Multi-band and wide-band metamaterial absorber for radar cross section reduction of an antenna - Md Ali, Siti Adlina (2022)
Metamaterial is a periodically arranged of unit cells with adjustable electric permittivity and magnetic permeability, which is enabled the production of electromagnetic (EM) materials with properties not observed in nature. A few types of metamaterials are used for different applications; High Impedance Surface (HIS), Artificial Magnetic Conductor (AMC), Frequency Selective Surface (FSS) and Metamaterial Absorber (MA). The aim of the MA is to decrease EM wave reflect to source by minimizing the reflection and eliminating the transmission. The transmission is blocked by the ground plane while the reflection is minimized depend on the impedance matching between the surface impedance and free space impedance. The MA is applied in Radar Cross Section (RCS) reduction to be invisibly tracked by the radar. Unfortunately, the recent studies are successfully achieved RCS reduction with either maintained or decreased the gain of the antenna. Therefore, this research is focused on the designed of multi-band MA and wide-band MA with high absorption for RCS reduction at the same time to enhance the gain of the antenna. The multi-band MA is designed based on bar patch, which is printed on Taconic TLY-5 with the thickness of 1.52 mm. The bar patch is rotated anticlockwise from 0o to 90o in 15o increment to understand the structure's absorption spectrum. At rotation of 45o, the bar patch MA is slotted to develop a multi-band MA. The multi-band MA is successfully maintained high absorption at each resonances; 3.98 GHz, 4.81 GHz, and 5.80 GHz with absorption of 99.94%, 99.88%, and 99.66% respectively. Then, the wide-band MA is designed based on double arrow connected with a lump resistor, which is printed on Taconic TLY-3 with the thickness of 0.25 mm. Due to the inherent limitation during fabrication and utilization in real applications, the resistor is replaced by the thin line to connect both arrows to represent the lump element resistance. A wide-band MA is resonated from 3.87 GHz to 11.25 GHz with triple absorption peaks at 4.17 GHz, 6.09 GHz, and 10.30 GHz with absorption capability of more than 99%. Then, the Meandered Dipole Antenna (MDA) is designed at 5.80 GHz to integrate with multi-band MA or wide-band MA to study the RCS reduction and gain enhancement. Both integration are successfully achieved more than -25 dBsm of low RCS apart of enhanced more than 3 dB gain of the antenna. Therefore, the multi-band MA and wide-band MA with high absorption turns out to be suitable for a wide variety of potential applications for Low Observable Technology (LOT) in stealth communication technology.